2023
DOI: 10.1039/d3ra00039g
|View full text |Cite
|
Sign up to set email alerts
|

Optical performance analysis of InP nanostructures for photovoltaic applications

Abstract: The optical performance of different indium phosphide (InP) nanostructures are investigated using Wave Optics Module of COMSOL Multiphysics. Our results indicate that InP based nanostructures outperform silicon based nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Examining a material’s physical characteristics can assist us in comprehending the condition of a material system and reveal potential applications for a substance. For the analysis of the optical and electronic contribution of various elements in a perovskite solar absorber material, various optical and electronic properties such as band gap and band structure, density of states (DOS), and charge density distribution are essential to explore. Nowadays, scientists use the DFT technique to conduct a theoretical investigation of the physical characteristics of relevant materials. However, a few experimental and theoretical works have been found on the titled perovskite. This compound was successfully prepared by López et al using a mechanochemical process in a N 2 atmosphere, which revealed a phase transformation from orthorhombic (S.G: Pbnm , #62) to cubic (S.G: Pm 3̅ m , #221) symmetry above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Examining a material’s physical characteristics can assist us in comprehending the condition of a material system and reveal potential applications for a substance. For the analysis of the optical and electronic contribution of various elements in a perovskite solar absorber material, various optical and electronic properties such as band gap and band structure, density of states (DOS), and charge density distribution are essential to explore. Nowadays, scientists use the DFT technique to conduct a theoretical investigation of the physical characteristics of relevant materials. However, a few experimental and theoretical works have been found on the titled perovskite. This compound was successfully prepared by López et al using a mechanochemical process in a N 2 atmosphere, which revealed a phase transformation from orthorhombic (S.G: Pbnm , #62) to cubic (S.G: Pm 3̅ m , #221) symmetry above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic metal halide perovskites with the structural formula of AMX 3 (A = organic group; M = metal ion; and X = halide ions) have emerged as viable contenders for perovskite solar cell (PSC) technologies due to their exceptional optoelectronic properties such as tunable band gap, high absorption coefficient, extended diffusion lengths, efficient charge transport, and long carrier lifetimes. Although the lead-based perovskites show similar optical and electronic properties and have reached efficiencies exceeding 25%, which is comparable to that of crystalline silicon, their commercial application is still questionable due to the two major issues of toxicity and stability . These two factors drove the researchers to look for alternative materials for future PSCs considering the feasibility of commercialization. Initially, tin (Sn) and germanium (Ge) were considered effective replacements for Pb-based perovskites due to the similarity in their valence shell electronic configuration (all three being group 14 elements) . However, the PCEs of Sn- and Ge-based PSCs are limited by their chemical and atmospheric instabilities in the desired oxidation state …”
Section: Introductionmentioning
confidence: 99%
“…6–10 However, the major challenges faced by the photovoltaic (PV) industry with hybrid perovskite technology are its poor stability (it breaks down with time upon exposure to moisture, light, heat, and oxygen), and neurotoxin lead content, which make it unfit for long-term outdoor use and commercial sales, respectively. 11–15…”
Section: Introductionmentioning
confidence: 99%